Peran Guru dalam Membentuk Karakter Siswa: (Studi Kasus di MI Al-Khoeriyah Bogor) - Putri, Willa; Kurniawan, Muchamad Arif; Nuraini, Nuraini (Jayapangus Press, 2024)
The background of this research is based on the importance of the teacher's role in developing students' character as part of the national education goals, especially in Islamic schools. The main objective of this research is to explore the strategies applied by teachers in developing students‘ character and their impact on students’ moral and social development. The research used a qualitative method with a case study design, involving in-depth interviews, observation of classroom and extracurricular activities, and document analysis. Data were collected through direct interaction with teachers and students to understand how character is developed in that school context. The results show that teachers at MI Al-Khoeriyah Bogor adopt a holistic approach in implementing character education. Ethical, moral and spiritual values are integrated thoroughly in various school activities. The school successfully combines Islamic values with a character development programme that includes aspects of religion, honesty, social care, discipline, nationalism, mutual cooperation, independence, responsibility, tolerance and compassion. Character education is implemented through various approaches such as daily habituation, routine activities, and integration in formal learning. In addition, students are actively involved in activities that support character education. In conclusion, the character education approach at MI Al-Khoeriyah Bogor has been effective in creating a conducive learning environment for students' character development. Through the application of Islamic values and relevant activities, the school prepares students to become individuals with integrity, responsibility and care for society, in accordance with the objectives of national education.